Consumption and Gross Domestic Product Dynamic – Empirical Research and Results - Ivanova, Tatiana (Research Papers, 2020)
This article is a scientific review of empirical research on the role of consumption in the economy. Consequently, studies on aggregate consumption and energy consumption are presented, with a place of publication for Bulgaria. The position of the authors, as well as the results of their analysis, are contradictory, do not lead to a conclusive conclusion and there is no overall causal link. The research results testify that none of the economic doctrines is capable of making universal recommendations, the blind follow-up of which will ensure economic policy success and the sustainability of the economic system.